C2H2 zinc finger-SET histone methyltransferase is a plant-specific chromatin modifier - Krichevsky, Alexander (2006)
Histone modification represents a universal mechanism for regulation of eukaryotic gene expression underlying diverse biological processes from neuronal gene expression in mammals to control of flowering in plants. In animal cells, these chromatin modifications are effected by well-defined multiprotein complexes containing specific histone-modifying activities. In plants, information about the composition of such co-repressor complexes is just beginning to emerge. Here, we report that two Arabidopsis thaliana factors, a SWIRM domain polyamine oxidase protein, AtSWP1, and a plant-specific C2H2 zinc finger-SET domain protein, AtCZS, interact with each other in plant cells and repress expression of a negative regulator of flowering, FLOWERING LOCUS C (FLC) via an autonomous, vernalization-independent pathway. Loss-of-function of either AtSWP1 or AtCZS results in reduced dimethylation of lysine 9 and lysine 27 of histone H3 and hyperacetylation of histone H4 within the FLC locus, in elevated FLC mRNA levels, and in moderately delayed flowering. Thus, AtSWP1 and AtCZS represent two main components of a co-repressor complex that fine tunes flowering and is unique to plants.